2006
DOI: 10.1111/j.1479-8425.2006.00220.x
|View full text |Cite
|
Sign up to set email alerts
|

Restless legs syndrome and its correlation with other sleep problems in the general adult population of Japan

Abstract: The epidemiological study presented here was conducted to examine the association between sleep problems and restless legs syndrome (RLS) among a large sample taken from the general population of Japan. The presence of RLS was established by asking the subjects if they experienced a crawling sensation in their legs after going to bed. This survey was performed in June 2000, targeting a sample that was randomly selected from 300 communities throughout Japan. The questionnaire contained questions focusing on hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…This means that the estimated OR of DMS was not established. These results were quite similar to those of a study of the general Japanese population by Enomoto et al 14 In their study the OR with regard to RLS were DIS (2.58), EDS (2.28), DMS (1.71), SIS (1.36) and EMA (1.21). Manconi et al also pointed out an association with EDS.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This means that the estimated OR of DMS was not established. These results were quite similar to those of a study of the general Japanese population by Enomoto et al 14 In their study the OR with regard to RLS were DIS (2.58), EDS (2.28), DMS (1.71), SIS (1.36) and EMA (1.21). Manconi et al also pointed out an association with EDS.…”
Section: Discussionsupporting
confidence: 91%
“…This value is similar to previously reported values (1.06%, 12 1.5%, 13 and 3.0% 14 ) for the prevalence of RLS among the general population in Japan. It is known that the prevalence of RLS in Western countries is higher [15][16][17][18][19][20] (in the range of 5.5-14.3%) than that in other countries, including Asian countries [12][13][14][21][22][23][24] (in the range of 0.1% to 3.19%). Genetic differences were suggested 7,25,26 as a reason for this difference.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, difficulty in sleep initiation and repeated awakening during the night were the first and second most prevalent complaints, respectively, which was in accordance with a previous study in Japan showing a strong association of RLS with difficulty during sleep initiation. 26 About half of the patients reported that their symptoms usually began at bedtime, but 38.7% suffered from leg disturbance while awake throughout the day.…”
Section: Discussionmentioning
confidence: 99%